4CPS-086 A fully integrated clinical trial-like system to manage and monitor persistence in planned hepatitis C treatment. (March 2019) - Gomes, I; Figueira, A; Sequeira, C; Ferreira da Silva, S; Machado, F; Figueiredo, P; Rabadão, E; Andreozzi, V; Félix, J; Feio, J
Abstract : Background: Portugal was one of the first countries in the world to have a universal access programme to new direct-acting antivirals (DAA) therapy for hepatitis C. The implementation of such a policy in our university hospital was managed by the hospital pharmacy based on a new and specific system designated fully integrated clinical trials-like system (CTLIKE), allowing full traceability of hepatitis C therapy and patient outcomes. Purpose: Our aim was to assess CTLIKE system efficiency in terms of patients' persistence on DAA therapy for hepatitis C in our hospital. Material and methods: CTLIKE is based on a set of day-to-day routines and protocols, supported by a dedicated software with the aim of controlling DAA dispensing and refiling, and also therapy and patient outcomes monitoring, with the ultimate goal of capturing full benefits from hepatitis C treatment for all stakeholders involved. CTLIKE is managed by the hospital pharmacy in our university hospital. The efficiency of CTLIKE was assessed by measuring persistence, defined as remaining in therapy and not discontinuing (end of treatment). The Kaplan–Meier method was used for crude survival calculations. The risk of DAA treatment discontinuation was estimated by Cox proportional hazard models. Adherence was a secondary exploratory endpoint calculated by the pill count method. Results: Data supporting this research was retrospectively collected and refers to 721 patients initiating DAA therapy since January 2015. Mean (SD) age at therapy initiation was 49.9 (10.8) years and 76.0% were male: genotype 1 (70.8%), metavir F1 (33.3%) and treatment naïve (69.5%). The vast majority of treatment regimens were sofosbuvir-based (94.7%). Programmed treatment duration was: 12 weeks (73.6%) and 24 weeks (26.4%). Premature treatment discontinuation before the planned 12 and 24 weeks was estimated at 9.5% (95% CI: 6.9% to 12.1%) and 20.4% (95% CI: 14.4% to 26.0%), respectively. Non-cirrhotic patients (HR discontinuation=0.73, 95% CI: 0.57 to 0.95) and males (HR=0.85, 95% CI: 0.69 to 1.04) were more likely to persist in treatment. Adherence level ≥95% to DAA treatment (pill count) occurred in 97.8% and 98.9% of the 12 weeks and 24 weeks subgroups. Conclusion: The CTLIKE system revealed full efficacy in DAA dispensing and hepatitis C treatment outcomes monitoring, guaranteeing very high persistence and adherence rates in hepatitis C therapy in this real-world setting. References and/or acknowledgements: None. No conflict of interest.